Climatic Analysis and Climatic Water Balance Determination for Al- Yusufiyah Area, Southern Baghdad, Iraq - Al-Dabbas, Moutaz A.; Razzaq, Saad M. Abdul (Iraqi Journal of Science, 2021)
The Climatic parameters for the years (1985-2015) were collected from Baghdadmeteorological station and then were applied to evaluate the climatic conditions forthe Al-Yusufyiah area south Baghdad. The total annual rainfall is (119.65 mm),while the total annual evaporation is (3201.7 mm), relative humidity is (43.62%),sunshine (8.76 h/day), temperature (23.28 C◦) and wind speed (3.06 m/sec). Climateof the study area is described as an arid according to classification of (Kettaneh andGangopadhyaya, 1974), (Mather, 1973), and (Al-Kubaisi, 2004). Mean monthlywater surplus for the period (1985-2015) was recorded in the study area about (4.7mm) in November, (11.67 mm) in December, (20.56 mm) in January and (6.51mm)in February of the whole amount of Rainfall and equivalent to (119.65 mm).